Reestructuración financiera como mecanismo para incrementar el valor patrimonial de la empresa Almacenes Populares S.R.L - Florentino Epiquién, Lenin (2016)
In this research it was evaluated the advisability of implementing a financial restructuring of the company Almacenes Popular S.R.L. of wholesale trade category, using the methodology of business valuation. Building two scenarios depending on the inclusion or not of such a restructuring. The results were as expected, it is found that the implementation of the financial restructuring increases the value of the company and equity in S/.1,099,697 and S/.2,285,549 respectively, and rates of 10.5% and 11.6% for WACC and COK respectively. The enterprise value is increased due to the fact that in the scenario "with restructuring" take advantage for a greater proportion (50% of the billing) of discounts for prompt payment (2.5% of the purchase price) granted by the main suppliers of the company. The value of equity in the scenario "with restructuring" is increased in addition to the previous reason, due to the saving in financial expenses of approximately -1.5pp of TCEA (from 9% to 7.5%).g (factoring) and thus saves inherent financial expenses.